2020
DOI: 10.1038/s41598-020-73928-x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of glioma resection in the corpus callosum

Abstract: Due to anticipated postoperative neuropsychological sequelae, patients with gliomas infiltrating the corpus callosum rarely undergo tumor resection and mostly present in a poor neurological state. We aimed at investigating the benefit of glioma resection in the corpus callosum, hypothesizing neuropsychological deficits were mainly caused by tumor presence. Between 01/2017 and 1/2020, 21 patients who underwent glioma resection in the corpus callosum were prospectively enrolled into this study. Neuropsychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…However, resection with low persistent neurological deficits and without long-term decline is possible. The use of neuronavigation and subcortical mapping might improve safety and outcomes 6 , 14 . Sughrue 20 described the key points in resecting of the anterior, the middle callosum, and the splenial bGBM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, resection with low persistent neurological deficits and without long-term decline is possible. The use of neuronavigation and subcortical mapping might improve safety and outcomes 6 , 14 . Sughrue 20 described the key points in resecting of the anterior, the middle callosum, and the splenial bGBM.…”
Section: Discussionmentioning
confidence: 99%
“…Burks et al 21 presented evidence for the safe removal of anterior bGBM during awake brain surgery. Forster et al 6 concluded that the benefit of tumor resection might outweigh morbidity in patients with a preoperatively good neurological state. Moreover, the quality of life in patients who had a resection was improved compared with biopsy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ccGlioma was also considered to have a higher incidence of PDGFRA alterations than non-ccGlioma in a previous study (Shen et al, 2020). Furthermore, ccGlioma was indicated to have a poorer prognosis than non-ccGlioma, and ccGBM had an even shorter median OS, ranging from 7.0 to 15.0 months after surgery (Dziurzynski et al, 2012;Chaichana et al, 2014;Chen et al, 2015;Burks et al, 2017;Dayani et al, 2018;Opoku-Darko et al, 2018;Forster et al, 2020;Franco et al, 2020). Therefore, we hypothesized that PDGFRA alterations may play an important role in GBM and lead to a higher incidence of CC invasion and a poorer prognosis.…”
Section: Comparison Of Ccgbm With Diffuse Midline Gliomamentioning
confidence: 94%
“…Post-operative MRIs were obtained within 72 h after surgery by a senior neuroradiologist to determine the extent of the resection ( 21 ). Gross total resection was defined as a resection without residual Gd-enhancement, whereas subtotal resection was considered any resection with residual Gd-enhancement and an extent of resection ≥90% ( 22 ).…”
Section: Methodsmentioning
confidence: 99%